2017
DOI: 10.1515/fiqf-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foreign Equity Ownership on Corporate Social Responsibility: Empirical Evidence from Poland

Abstract: In the literature on corporate social responsibility (CSR) the origin of the equity is seen as one the drivers of CSR. There is evidence of multinational corporations stimulating diffusion of CSR practices in a few emerging economies. There are no similar studies focusing on the Polish economy. Since CSR practices are country-specific it is important to investigate if and how capital flows foster corporate social responsibility among firms established and operating in Poland. The method applied in the study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Study by Sunreni (2016) also states that foreign companies such as from Europe, Singapore, and America have more knowledge of CSR concepts and practices so these companies are known to care more about social and environmental issues. The same results were revealed in Do (2017), A. H. Hu et al (2016).…”
Section: Foreign Ownership and Csr Disclosuresupporting
confidence: 80%
See 1 more Smart Citation
“…Study by Sunreni (2016) also states that foreign companies such as from Europe, Singapore, and America have more knowledge of CSR concepts and practices so these companies are known to care more about social and environmental issues. The same results were revealed in Do (2017), A. H. Hu et al (2016).…”
Section: Foreign Ownership and Csr Disclosuresupporting
confidence: 80%
“…In line with stakeholder theory, if a company has a trade or ownership agreement with a foreign party, it will disclose CSR-related information more broadly (Asrida, 2011). Do (2017), Hu et al (2016), andSunreni (2016) also found that the concerns and responsibilities of foreign shareholders regarding social and environmental issues are profound. Examples of countries that are more concerned with environmental conditions are America and Europe (Sunreni, 2016).…”
Section: Foreign Ownership and Csr Disclosurementioning
confidence: 95%
“…Based on studies conducted by Nyarku and Hinson (2018); Porter (1990); Kuada & Hinson (2012); Doś (2018), it is unveiled that foreign banks have higher scores than national banks in terms of social and environmental issues (green banking). Furthermore, Khanna & Palepu (2000) found a significant difference in performance between foreign and domestic companies.…”
Section: Role Of Ownership Structure (Foreign and Public) On The Assomentioning
confidence: 99%
“…However, Kim et al (2018), for example, cannot prove this effect. On the other hand, foreign bank ownership has a positive effect on Environmental, Social, and Corporate Governance (ESG) investment (see Nyarku & Hinson, 2018;Doś, 2018). Using a sample of government companies listed on the Europe market, Danford (2017) found that ESG decreases corporate performance.…”
Section: Introductionmentioning
confidence: 99%
“…Continuously discussing the ownership structure of banks, Based on Financial Services Authority Regulation Number 12/POJK.03/2021 regarding Commercial Banks, foreign parties can own shares in the industrial sector in Indonesia up to 99% and foreign share ownership has a minimum limit of IDR 10 billion (excluding land price and buildings) and the minimum amount that must be deposited with Bank Indonesia is IDR 2.5 billion. based on the research results of Doś (2017), it shows that foreign banks have higher scores in terms of social and environmental involvement (green banking). Companies controlled by foreign parties or investors are considered to perform better because they have better transparency and control options.…”
Section: The Backgroundmentioning
confidence: 99%